Student Motivation and Expectations in the Implementation of On-the-Job Training Program (Case Study on XYZ School Students) - Wulanmeiaya Wowor; Samuel Musa Liha; Andrew Kurniawan; Randy Setiadi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
On-the-job training (OTJT) is one of the learning programs that are widely applied by vocational schools. Through this program, students can gain new skills and get new experience in the industry. Students also have the opportunity to apply their knowledge and develop their skills. This study aims to identify the motivation and expectations of students in carrying out the OTJT. The research method used is descriptive quantitative with a purposive sampling technique in determining the sample. Questionnaires were used to collect data. Respondents are XYZ school students who have participated in the OTJT as many as 163 people. The results of this study found that in the implementation of the OTJT, interesting work is the thing that motivates students the most, while the low wage factor is the thing that reduces motivation. In addition, working in a professional environment is the most expected thing to be experienced when participating in the OTJT program. Keywords — Expectation, Motivation, On the job training